Technology transfer from public research organizations: Japanese experience - Nga, Nguyen Thi Minh; Hai, Nguyen Hoang; Trang, Dang Thu; Huyen, Tran Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Technology transfer is a complex process that requires delivery suitable methods and channels for each object to achieve the desired effect. One of the official technology transfer channels from universities and public research institutes (public research organizations) to enterprises is the process of cooperation between the academic sector and the industrial sector. In this paper, we focus on technology transfer from Japanese public research institutions to private enterprises, in other words, the cooperation between the academic and industrial sectors. Code: 19010701